The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s10886-012-0129-3
|View full text |Cite
|
Sign up to set email alerts
|

Tracing Hidden Herbivores: Time-Resolved Non-Invasive Analysis of Belowground Volatiles by Proton-Transfer-Reaction Mass Spectrometry (PTR-MS)

Abstract: Root herbivores are notoriously difficult to study, as they feed hidden in the soil. However, root herbivores may be traced by analyzing specific volatile organic compounds (VOCs) that are produced by damaged roots. These VOCs not only support parasitoids in the localization of their host, but also may help scientists study belowground plant-herbivore interactions. Herbivore-induced VOCs are usually analyzed by gas-chromatography mass spectrometry (GC-MS), but with this off-line method, the gases of interest n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 67 publications
(102 reference statements)
1
52
0
Order By: Relevance
“…GC-MS and proton transfer reaction-mass spectrometry (PTR-MS) analyses have shown that insect-damaged Brassica roots release mainly highly volatile sulphur compounds (methanethiol, dimethyl sulphide, dimethyl disulphide and dimethyl trisulphide) and glucosinolate breakdown products (thiocyanates and isothiocyanates) in the soil, with a VOC emission pattern depending on the plant species studied Danner et al 2012;Crespo et al 2012;Danner et al 2015). To date, PTR-MS analyses of root-emitted VOCs have been performed only on potted Brassica spp.…”
Section: Td-gc-msmentioning
confidence: 99%
See 3 more Smart Citations
“…GC-MS and proton transfer reaction-mass spectrometry (PTR-MS) analyses have shown that insect-damaged Brassica roots release mainly highly volatile sulphur compounds (methanethiol, dimethyl sulphide, dimethyl disulphide and dimethyl trisulphide) and glucosinolate breakdown products (thiocyanates and isothiocyanates) in the soil, with a VOC emission pattern depending on the plant species studied Danner et al 2012;Crespo et al 2012;Danner et al 2015). To date, PTR-MS analyses of root-emitted VOCs have been performed only on potted Brassica spp.…”
Section: Td-gc-msmentioning
confidence: 99%
“…Due to their belowground location, studying root-root interactions mediated by VOCs is challenging and requires innovative tools in order to (1) identify the volatile signals released into the plant rhizosphere Campos-Herrera et al 2013;Hiltpold et al 2013), (2) follow the temporal variations in VOC emission (composition of the VOC blends and individual VOC concentrations) (Danner et al 2012) and (3) conduct bioassays on the roles played by root-emitted VOCs in plant-plant interactions.…”
Section: Technical Challenges and Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…Of particular relevance is the finding that the changing profile of organosulfur exudates that occurs in Brassica spp. roots in response to herbivore attack or a tissue breach can be monitored in real time by proton transfer reaction-mass spectrometry (Crespo et al, 2012;Danner et al, 2012;van Dam et al, 2012;Samudrala et al, 2015). If conventional metabolome analysis sample preparation methods had been used in these cases (e.g.…”
Section: Discussionmentioning
confidence: 99%